Teaching in Uncertain Times: Expanding the Scope of Extraneous Cognitive Load in the Cognitive Load Theory - Taylor, Tracey A. H.; Kamel-ElSayed, Suzan; Grogan, James F.; Hajj Hussein, Inaya; Lerchenfeldt, Sarah; Mohiyeddini, Changiz (Frontiers in Psychology, 2022)
Globally, the COVID-19 pandemic has forced medical education towards more “online-education” approaches, causing specific implications to arise for medical educators and learners. Because the COVID-19 pandemic caused an unprecedented and highly threatening, constrained, and confusing social and educational environment, we decided to expand the traditional focus of the extraneous load in Cognitive Load Theory (CLT) and, following Mohiyeddini (sub.) acknowledge the psychological environment in which learning occurs. Accordingly, “Learning and instructional procedures do not occur in a situational vacuum” (page 1). We therefore adapted and implemented principles of the CLT in order to reduce extraneous load for our students by facilitating their educational activities. The adoption of these principles enabled our students to cultivate attitudes and skills across multiple domains such as online learning and presentation technologies, implementing and maintaining a “classroom atmosphere” in a virtual environment, participating in discussions among large online groups of students, facilitating group work, providing virtual office hours for our students, and proactively planning for the upcoming semesters.